PENERAPAN METODE TALKING STICK BERBANTUAN PETA TEMATIK UNTUK MENINGKATKAN HASIL BELAJAR IPS - Choirunisya, Hapsari (Jurnal Pena Ilmiah, 2017)
This study was conducted to improve the process and the results of student learning on the local environment map reading material. Alternative troubleshooting is selected by applying the talking stick method. Subjects in this study were students of SDN Sindang II which amounted to 19 people. This classroom action research is conducted in three cycles. Based on preliminary data obtained by the result of student learning complete 37%, after implemented cycle I achievement of student learning result rose to 47,36%, in cycle II percentage of achievement increased become 73,68% and at cycle III percentage of student who complete 89,47 %. The achievement of student activity in cycle I 63,15%, in cycle II percentage achievement 78,94% and in cycle III reach 89,47%. Student learning outcomes and activities have reached the target 85%. Thus it can be concluded that the application of the talking stick method can improve the learning outcomes of Social studies on the local environment map reading material.